The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/mcn.13273
|View full text |Cite
|
Sign up to set email alerts
|

Traditional prenatal and postpartum food restrictions among women in northern Lao PDR

Abstract: Culturally determined food restrictions are common among pregnant and postpartum women in Asia. This study aimed to describe perinatal dietary restrictions, factors associated with food avoidances and attainment of minimum dietary diversity (MDD-W) among women in Lao PDR. Mother-child (aged 21 days to <18 months) dyads (n = 682) were enrolled into a cohort study in northern Lao PDR and interviewed at one time point postpartum. During pregnancy and postpartum, 1.6% and 97% of women reported following dietary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…ANC and supplementation utilisation may be low due to physical, geographical and financial factors but may also be influenced by cultural factors and traditional ideas and beliefs surrounding pregnancy and childbirth (41,59) . In Lao PDR, dietary restrictions and food avoidances are commonplace during the perinatal period, especially postpartum (31,32) , and it remains relatively unexplored if supplements are culturally acceptable during this restrictive period. A high proportion of women (86⋅3 %) in the present study reported that they would be willing to take supplements during the period of postpartum dietary restrictions if provided to them by health facilities, indicating that these may be culturally acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ANC and supplementation utilisation may be low due to physical, geographical and financial factors but may also be influenced by cultural factors and traditional ideas and beliefs surrounding pregnancy and childbirth (41,59) . In Lao PDR, dietary restrictions and food avoidances are commonplace during the perinatal period, especially postpartum (31,32) , and it remains relatively unexplored if supplements are culturally acceptable during this restrictive period. A high proportion of women (86⋅3 %) in the present study reported that they would be willing to take supplements during the period of postpartum dietary restrictions if provided to them by health facilities, indicating that these may be culturally acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…As culturally determined restrictive postpartum diets are common in the study population, a comprehensive questionnaire was developed to interview women about their diets during pregnancy and postpartum, as previously described in detail (32) . This included the determination of what foods and condiments (salt, fish sauce and soy sauce) were consumed or restricted in weekly (for the first 4 weeks) and monthly intervals postpartum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, vitamins are commonly recommended by physicians, but other bioactive compounds are overlooked. Moreover, nutritional programs that include a nutritionist do not normally accompany pregnancies; however, some women often resort to strict diets in the postpartum stage [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy reliance on rice with limited animal protein contributes to nutritional deficiencies 27. In northern Lao PDR, newborns are commonly fed masticated sticky rice after birth, and 97% of women report following culturally determined restricted diets for one or more months postpartum, reducing consumption of all food groups, except rice 28…”
Section: Introductionmentioning
confidence: 99%